Identification of an immune modulation locus utilising a bovine mammary gland infection challenge model. Issue 2 (22nd May 2018) - Littlejohn, Mathew D; Turner, Sally-Anne; Walker, Caroline G; Berry, Sarah D; Tiplady, Kathryn; Sherlock, Ric G; Sutherland, Greg; Swift, Simon; Garrick, Dorian; Lacy-Hulbert, S Jane; McDougall, Scott; Spelman, Richard J; et al.
Abstract : Inflammation of the mammary gland following bacterial infection, commonly known as mastitis, affects all mammalian species. Although the aetiology and epidemiology of mastitis in the dairy cow are well described, the genetic factors mediating resistance to mammary gland infection are not well known, due in part to the difficulty in obtaining robust phenotypic information from sufficiently large numbers of individuals. To address this problem, an experimental mammary gland infection experiment was undertaken, using a Friesian-Jersey cross breed F2 herd. A total of 604 animals received an intramammary infusion of Streptococcus uberis in one gland, and the clinical response over 13 milkings was used for linkage mapping and genome-wide association analysis. A quantitative trait locus (QTL) was detected on bovine chromosome 11 for clinical mastitis status using micro-satellite and Affymetrix 10 K SNP markers, and then exome and genome sequence data used from the six F1 sires of the experimental animals to examine this region in more detail. A total of 485 sequence variants were typed in the QTL interval, and association mapping using these and an additional 37 986 genome-wide markers from the Illumina SNP50 bovine SNP panel revealed association with markers encompassing the interleukin-1 gene cluster locus. This study highlights a region on bovine chromosome 11, consistent with earlier studies, as conferring resistance to experimentally induced mammary gland infection, and newly prioritises the IL1 gene cluster for further analysis in genetic resistance to mastitis.